Myocardial work of the athlete's heart: the new champion of systolic function?. (25th November 2020) - Tokodi, M; Olah, A; Ruppert, M; Lakatos, B.K; Fabian, A; Ladanyi, Z.S; Karime, C; Sayour, A.A; Barta, B.A; Csulak, E; Sydo, N; Kiss, O; et al.
Abstract: Background: Regular, vigorous exercise induces morphological changes in the heart, including increased left ventricular (LV) volumes and mass. Although this represents a physiological adaptation to the increased cardiovascular demand, in a certain number of highly trained athletes, the LV remodelling is accompanied by decreased resting values of global longitudinal strain (GLS), exceeding even pathological limits. In this case, the differential diagnosis of overlapping pathological conditions represents a clinical challenge. Myocardial work (MW) evaluates myocardial deformation in the context of afterload; therefore, it may potentially overcome the limitations of GLS, and may better reflect the contractility of the athlete's heart. Purpose: We sought to evaluate MW of elite athletes compared to sedentary volunteers. We also aimed to validate its robustness by investigating its relation to the invasively measured parameters of myocardial contractility in a rat model of the athlete's heart. Methods: A total of 30 elite swimmers (19±4 years, 23±5 hours of training/week, 50% males) and 23 healthy sedentary controls (19±4 years, 40% males) were enrolled. Global MW index (GMWI) and constructive MW index (CMWI) were calculated using a vendor-specific module through the simultaneous evaluation of GLS by speckle-tracking echocardiography (STE) and the non-invasively approximated LV pressure curves (estimated from brachial cuff systolic pressure). In the rat model, LV hypertrophy was induced by swim training (n=18, 200 min/day for 12 weeks). An additional group of 17 untrained control rats were examined as well. STE was performed to assess GLS, which was followed by invasive pressure-volume (P-V) analysis to register LV pressure and to calculate cardiac contractility (slope of end-systolic P-V relationship [ESPVR]). GMWI and CMWI were assessed by evaluating the area of the LV pressure-strain loop. Results: GLS was decreased in human athletes (athletes vs. controls: −18±2 vs. −19±1, p<0.05). However, athletes had higher values of CMWI (2097±293 vs. 1943±213 mmHg%, p<0.05), whereas GMWI was unchanged compared to controls (1850±299 vs. 1755±189 mmHg%, p=NS). The trained group of rats was characterized by unchanged GLS (−22±3 vs. −20±4, p=NS), however, ESPVR, GMWI, and CMWI were increased (3.64±0.70 vs. 2.55±0.38 mmHg/μL, p<0.001; 3002±488 vs. 2554±375 mmHg%, p<0.05; 3200±532 vs. 2780±591 mmHg%, p<0.05) compared to control rats. MW indices correlated with cardiac contractility measured by P-V analysis (ESPVR vs. GMWI r=0.38, p<0.05; vs. CMWI r=0.39, p<0.05). Conclusions: Due to the adaptive LV remodelling, resting markers of LV systolic function may be decreased in elite athletes. Despite the reduced GLS, GMWI was preserved, and CMWI was supernormal in human athletes and the experimental model verified their correlation with contractility. Our findings indicate that MW indices in athletes may be better markers of systolic function compared to GLS. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office of Hungary